The Relationship Between Strategic Leadership and Organizational Culture of Teachers Under the office of Chachoengsao Primary Educational Service Area Office 1: The Relationship Between Strategic Leadership and Organizational Culture of Teachers Under the office of Chachoengsao Primary Educational Service Area Office 1 - Toyai , Daranee; Silalaiy, Khukrit (RATANABUTH JOURNAL, 2025)
The objectives of this research were 1) to study of strategic leadership of education institution administrators under the office of Chachoengsao primary educational service area office 1 2) to study of organizational culture of teachers under the office of Chachoengsao primary educational service area office 1 and 3) to study of the relationship between strategic leadership and organizational culture of teachers under the office of Chachoengsao primary educational service area office 1. The sample group used in this research were 306 teachers under the office of Chachoengsao primary educational service area office 1. The instrument used to collect the data was questionnaire. Index of item objective congruence was between 0.80 to 1.00, and the reliability was 0.985. The statistics used in the data analysis were frequency distribution, percentage, mean, standard deviation and Pearson’s product-moment correlation coefficient. The research findings were as follows: 1) The level of Strategic Leadership of school administrators Schools Under the office of Chachoengsao Primary Educational Service Area Office 1 as a overall and each aspect was at a high level. 2) The level of Organizational Culture of Teachers Under the office of Chachoengsao Primary Educational Service Area Office 1 as a overall and each aspect was at a high level. 3) The Relationship between Strategic Leadership and Organizational Culture of Teachers Under the office of Chachoengsao Primary Educational Service Area Office 1 as a whole and each aspect was positive relationship at high level. Overall were not significant difference at the .01